2003
DOI: 10.1046/j.1365-2141.2003.04469.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct selection of human bone marrow mesenchymal stem cells using an anti‐CD49a antibody reveals their CD45med,low phenotype

Abstract: Summary. Human bone marrow mesenchymal stem cells (MSC) generate, via a fibroblast colony-forming unit (CFU-F), osteo-chondroblastic cells as well as adipocytes and stromacytes. To date, these stem cells are isolated indirectly using a cell culture method and phenotyped as CD45 negative while the in vivo counterparts are undetermined. Our aim was to develop a direct selection method and to determine the phenotype of the MSC isolated in this way. Mesenchymal cells were selected with anti-CD49a and/or anti-CD45 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
99
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(113 citation statements)
references
References 66 publications
(106 reference statements)
10
99
3
Order By: Relevance
“…The data suggests that MIAMI, RS-1 and MAP cells are not identical but that they are potentially linked developmentally within the heterogeneous mesenchymal compartment. Since the expression of a particular immunophenotype depends more on the culture conditions than on the developmental status of a cell (Deschaseaux et al, 2003) it is hard to establish at this point how these different cells are positioned within a developmental hierarchy based on their molecular profile. However, based on their differentiation properties it would be reasonable to assume that MIAMI and MAP cells represent a more primitive developmental stage than RS-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The data suggests that MIAMI, RS-1 and MAP cells are not identical but that they are potentially linked developmentally within the heterogeneous mesenchymal compartment. Since the expression of a particular immunophenotype depends more on the culture conditions than on the developmental status of a cell (Deschaseaux et al, 2003) it is hard to establish at this point how these different cells are positioned within a developmental hierarchy based on their molecular profile. However, based on their differentiation properties it would be reasonable to assume that MIAMI and MAP cells represent a more primitive developmental stage than RS-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have demonstrated that a proportion of BM cells trafficking to the skeletal muscle might lose expression of CD45 (Issarachai et al, 2002b;Issarachai et al, 2002a). In addition, CD45 -mesenchymal BM cells could also contribute to muscle (Deschaseaux et al, 2003). These observations urged us to use markers other than CD45 to monitor cellular contribution from the BM to skeletal muscle SP cells.…”
Section: Cd452 -Muscle Cells Are Not Bm-derivedmentioning
confidence: 99%
“…The stem cell for the haematopoietic and mesenchymal systems remains elusive, as there is no known marker that identifies exclusively either the HSC, haematopoietic progenitor cells, or the MSC; yet the biology of the HSC has served to identify its presence among a heterogeneous population of CD34 + progenitor cells and other cells that also express CD34, such as endothelial cells and mast cells. Similarly, studies utilising antibodies to known MSC-associated markers, such as nerve growth factor receptor, CD49a or STRO-1 [106][107][108], have shown that progenitors, CFU-F, to MSCs can be enriched. Further discovery of novel surrogate markers, may serve in a similar fashion as the CD34 antigen has as the surrogate marker for the haematopoietic stem cell.…”
Section: Expert Opinionmentioning
confidence: 99%